The Influence Of The Employee Selection And Recruitment System On Employee Performance Mediated By Competence At Pt Shinta Indah Jaya - Djagat Cakra Buana Tunggal; Nina Nurani (International Journal of Artificial Intelligence Research, 2022)
This study aims to determine the effect of employee selection system on employee competence, determine the effect of employee recruitment on employee competence, determine the effect of employee competence on employee performance and competence can mediate the effect of selection system on employee performance and competence can mediate the effect of recruitment on employee performance at PT Shinta Indah Jaya. The research method used is descriptive and verification. The population in this study were 80 employees with saturated sample method sampling so that the number of samples was the same as the population. The data analysis method uses Path Analysis with Partial Least Square (PLS) using SmartPLS software version3.0.     The results of this study indicate that competency variables, selection and recruitment systems have a positive and significant effect on performance variables, selection and recruitment systems have a positive and significant effect on competency variables. And from the results of the mediation role shows that the role of competence as mediation is proven to affect the selection system on performance, but the role of competence is not proven to mediate the effect of recruitment on the performance of PT Shinta Indah Jaya employees.